1992
DOI: 10.1007/bf00010356
|View full text |Cite
|
Sign up to set email alerts
|

Soybean response to nodulation by bradyrhizobia differing in rhizobitoxine phenotype

Abstract: Rhizobitoxine-producing (RT +) strains of Bradyrhizobium japonicum, differing in their abilities to induce foliar chlorosis with 'Forrest' soybean (Glycine max [L.] Merr.), were evaluated for effects on short term shoot productivity, nodulation, N 2 fixation, and nodule protein production under greenhouse conditions. Soybeans were singly inoculated with washed suspensions of (Group II) USDA strains 31, 46, 76, 94, 110, 123 or 130. Strains USDA 110 and USDA 123 (Group I/Ia) were included as RT-controls. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…Previous short-term studies conducted under greenhouse conditions have shown that severe RT-induced chlorosis is accompanied by reductions in shoot dry weight, leaf surface area, leaf chlorophyll concentration and soluble leaf protein content (Teaney and Fuhrmann, 1992). In the present study, application of 7.5 mM KNO 3 significantly alleviated all of these symptoms.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Previous short-term studies conducted under greenhouse conditions have shown that severe RT-induced chlorosis is accompanied by reductions in shoot dry weight, leaf surface area, leaf chlorophyll concentration and soluble leaf protein content (Teaney and Fuhrmann, 1992). In the present study, application of 7.5 mM KNO 3 significantly alleviated all of these symptoms.…”
Section: Discussionsupporting
confidence: 62%
“…Separation of the bacteroids from the nodule cytosol was achieved by a homogenization-centrifugation procedure (Pfeiffer et al, 1983;Teaney and Fuhrmann, 1992). Separation of the bacteroids from the nodule cytosol was achieved by a homogenization-centrifugation procedure (Pfeiffer et al, 1983;Teaney and Fuhrmann, 1992).…”
Section: Nodule Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The RT sensitivity of bradyrhizobia/3-cystathionase differed among the strains examined, and values Of VRr ranged from -0.34 to -0.67% activity min -l #M -l RT. The strain yielding the most sensitive/3-cystathionase was USDA 94 which also has been shown to produce the greatest amount of RT among the strains investigated both in culture and as a nodule symbiont (Teaney and Fuhrmann, 1992). /3-cystathionase obtained from bradyrhizobia, soybean, E. coli, and spinach exhibited different inhibition kinetics (Figure 3).…”
Section: Rhizobitoxine Sensitivity Of /3-cystathionasementioning
confidence: 99%